Family Experience in Handling the Elderly in Cultural Aspects of Indonesia - Ni Made Riasmini; Junaiti Sahar; Yeti Resnayati (Jurnal Ners, 2013)
Introduction: Extended family culture still exists in Indonesia, and this makes it possible for an elderly person to live with a family. In Indonesia, generally an elderly person is highly respected. This research is meant to gain a picture of an experience that a family has in taking care of an elderly person from the aspect of Indonesian culture.Methods: The design implemented is descriptive phenomenology. The participant is the main caregiver taking care of 10 elderly people. The data is analyzed using Collaizi technique.Result: This research have been identi fi ed 4 themes i.e. 1) the reason for doing it is to fulfi ll the tasks as a member of a family, to reciprocate, to have satisfaction, but for the main caregiver it is just because of closeness and pity, 2) the burden of caring is physical, psychological, social and fi nancial, 3) the perception about culture value is the position and role of the elderly person in the family, and 4) the support or encouragement is obtained from the family and the community.Conclusion: The conclusion is that a family as the main supporting system for the elderly people possesses big responsibility in caring the elderly in accordance with the value of culture in Indonesia. The results of the research are expected to give information about the need of a family as the caregiver in caring the elderly so that a proper intervention form of family enforcement according to the Indonesian culture can be designed.